2020
DOI: 10.1155/2020/6427157
|View full text |Cite
|
Sign up to set email alerts
|

Near-Field HF-RFID and CMA-Based Circularly Polarized Far-Field UHF-RFID Integrated Tag Antenna

Abstract: This research proposes an integrated high-frequency (HF) and ultrahigh-frequency (UHF) passive radio frequency identification (RFID) tag antenna for near-field (13.56 MHz) and far-field (920–925 MHz) communication. This tag antenna is advantageous for the applications with lossy material in the near-field communication and mitigates polarization loss in the far-field communications. The HF-RFID tag antenna is of square spiral structure, and the circularly polarized UHF-RFID structure consists of a square loop … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…The copolarization and cross-polarization are consistent with LHCP and RHCP radiations, respectively. The AR can be determined from equation ( 15) as [49] ( ) 20 15 The simulated IBW and ARBW were 74.57% (4 -8.4 GHz) and 56.4% (4.3 -7.63 GHz, respectively), and the measured IBW and ARBW were 87.74% (4 -9 GHz) and 57.6% (4.2 -7.6 GHz, respectively). The simulated and measured results were agreeable.…”
Section: Resultsmentioning
confidence: 99%
“…The copolarization and cross-polarization are consistent with LHCP and RHCP radiations, respectively. The AR can be determined from equation ( 15) as [49] ( ) 20 15 The simulated IBW and ARBW were 74.57% (4 -8.4 GHz) and 56.4% (4.3 -7.63 GHz, respectively), and the measured IBW and ARBW were 87.74% (4 -9 GHz) and 57.6% (4.2 -7.6 GHz, respectively). The simulated and measured results were agreeable.…”
Section: Resultsmentioning
confidence: 99%
“…The co-pol and cross-pol electric fields between the transmitting and receiving antennas correspond to E co−pol and E cross−pol , which in turn correspond to VOLUME 11, 2023 RHCP and LHCP. The AR is determined by equation ( 4) [30].…”
Section: Figures 19(amentioning
confidence: 99%
“…In [7], a 4 × 4 dipole with hexagonal-shaped parasitic patches CP antenna array achieves an IBW of 27.7% (26.26 -34.71 GHz) and 3-dB ARBW of 28.5% (27)(28)(29)(30)(31)(32)(33)(34)(35)(36). In [8], a magnetoelectric dipole CP antenna achieves an IBW of 27.2% (4.77 -6.27 GHz) and 3-dB ARBW of 42.3% (4.1 -6.3 GHz).…”
Section: Introductionmentioning
confidence: 99%
“…In practical, the MTS layer is fixed to the underneath of antenna with plastic supporting posts at air‐gap of 0.25 λ o shown in Figure 1D. The modal analysis 71 is performed in full‐wave CST studio suite and antenna is designed in ANSYS HFSS solver. From Figure 2, it is observed that monopole antenna offers orthogonal radiation modes (mode‐1 and mode‐2).…”
Section: Antenna Configuration and The Investigation Of Cp Using Theo...mentioning
confidence: 99%